Mapping the future capacities of the International Federation of Red Cross and Red Crescent Societies - Feinstein International Center (Tufts Archival Research Center, 2005)
The Norwegian Red Cross, a member of the IFRC, has contacted the Feinstein Famine Center, asking it to lead a dedicated research process to propose areas where National Societiesâ special skills and strengths might be further utilised within the framework of the Federation, to suggest new modes of cooperation within the Federation, to analyze the cost benefits of providing certain key Federal services through individual members or small consortia, and finally to look at new modalities for financing, staffing and managing Federation national and regional delegations.